2008
DOI: 10.1149/1.2982881
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Polishing of Exfoliated III-V Layers

Abstract: The chemical mechanical polishing of III-V materials including GaAs, InP, InAs, and GaSb is investigated with sodium hypochlorite and citric acid solutions. It is found that the surfaces can be polished to below 0.5 nm RMS surface roughness without the induction of crystalline damage using similar abrasive-free polishing solutions for all the materials with controlled polishing rates of 10 nm / min which is important for touch polishing of exfoliated III-V layers. The optimal composition of the slurry is adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…the full width at thousandth maximum (FW(0.001)M), from the pre-anneal state (310") to this annealed state (515") as shown in Figure 1b. While FWHM values are more commonly reported, previous work 21,25 demonstrated that the tails of ω peaks are more sensitive to changes in crystallinity, i.e. mosaicity or tilt in the exfoliated layer.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…the full width at thousandth maximum (FW(0.001)M), from the pre-anneal state (310") to this annealed state (515") as shown in Figure 1b. While FWHM values are more commonly reported, previous work 21,25 demonstrated that the tails of ω peaks are more sensitive to changes in crystallinity, i.e. mosaicity or tilt in the exfoliated layer.…”
Section: Resultsmentioning
confidence: 97%
“…This is a common occurrence observed in previous work with implanting other semiconductor materials. [18][19][20][21][25][26][27][28][29][30] The furthest left fringe in the ω:2θ scan typically corresponds to the maximum strain in the implanted region, 19 which is about 1.01%. The strain oscillation intensity decreased and shifted slightly after annealing at 200°C for 12 hours as shown in the ω:2θ scan in plots (i) through (iii) of Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations